Synthesis of Gallium Doped Mesoporous KIT-6 for the Photocatalytic Degradation of Dyes - Sanjini, N.S. (Asian Journal of Chemistry, 2013)
Gallium doped highly ordered three dimensional la3d mesoporous KIT-6 material was synthesized by simple impregnation procedure with an aqueous solution of Ga(NO3)3·H2O. Different concentrations of gallium were doped onto KIT-6. The incorporation of gallium on the surface of KIT-6 was confirmed by various characterization techniques such as X-ray diffraction, BET surface area, Fourier transform infrared spectroscopy and diffuse reflectance spectroscopy. The XRD confirms the 3D structure of the materials. KIT 6 and the gallium doped KIT 6 show very high surface area and pore diameter. The UV DRS spectrum of the prepared materials shows absorbance in UV-visible region indicates their potential application in photocatalytic reaction. Photodegradation of methylene blue with Ga-KIT-6 under visible and ultra violet light were followed by UV visible spectrophotometer. The complete degradation of methylene blue dye was observed within 135 min and the optimization studies for the photocatalytic degradation of dyes were also systematically done.